Characteristics of annealed glutinous rice flour and its formation of fast-frozen dumplings. (January 2018) - Li, Yue; Ding, Guangqin; Yokoyama, Wallace; Zhong, Fang
Abstract: In this study, characteristics of glutinous rice flour annealed in different conditions were evaluated, and qualities of fast-frozen dumplings made with these annealed flour were determined. Three kinds of annealed glutinous rice flour obtained under different conditions (ANN1, 55% moisture, 50 °C, 4 h; ANN2, 55% moisture, 50 °C, 6 h and ANN3, 50% moisture, 55 °C, 6 h) showed higher resistant starch content (5.92%–11.67% of the whole flour), gelatinization temperature and storage modulus of the pastes. The breakdown and setback values were decreased and temperature range of gelatinization was narrowed from 14.5 °C to around 12 °C. The glutinous dumplings made of annealed flour showed better freezing, storage and boiling qualities, especially the lower cracking rate, water loss, hardness and better sensory quality. It was notable that the boiled dumplings made of annealed flour had slower in vitro digestion rate, due to the increased resistant starch content (8.62%–15.25%) caused by the annealed treatment. Highlights: Annealing increases resistant starch content of glutinous rice flours and dumplings. Annealing changes the physicochemical properties of glutinous rice flour. Annealing improves freezing, storage and sensory properties of fast-frozen dumplings.